Pembiasaan Aktivitas Keagamaan untuk Meningkatkan Kecerdasan Spiritual Siswa SDN Penggung 1 Cirebon - Nurkholis, Nurkholis; Aulia, Anggi; Putra, Arildwika; Putri, Diva Aurelia; Miskah , Desti Aulia (Universitas Pahlawan Tuanku Tambusai, 2025)
High intellectual and emotional intelligence does not necessarily have good behavior, which is a phenomenon that occurs. The purpose of this study was to find out how the habituation of religious activities to improve the spiritual intelligence of students at SDN Penggung 1 Cirebon. This study investigates the efforts of teachers at SDN Penggung 1 Cirebon to improve students' spiritual intelligence by teaching them to read the Qur'an and pray. In addition, this study also investigates the role of parents and supporting and inhibiting factors in improving students' spiritual intelligence at SDN Penggung 1 Cirebon. This study was conducted using a qualitative descriptive method with data collection tools, interviews, observations, and documentation. In this study, the sample was only grades 4 to 6 because other classes had been sent home, the number of interviewees was 5 students, and 1 PAI teacher. This study was conducted at SDN Penggung 1 Cirebon Jln. Jendral Soedirman Gg. School, the research implementation period lasted for 3 months starting from March to June 2025. The results of the study showed that teachers' efforts to improve students' spiritual intelligence through the habit of reading the Qur'an, performing congregational prayers, infaq every Friday, PHBI such as the pesantren kilat ramadhan program, isro mi'raj, and the prophet's birthday. The study also showed that the role of parents is very important in improving children's spiritual intelligence.